Elucidating the challenges to Bumiputera entrepreneurs’ participation in the domestic furniture and wood products market in Malaysia - Ratnasingam, Jegatheswaran; Othman, Kamaruzaman; Amir, Mohd. Afthar; Jegatheswaran, Natkuncaran; Ab Latib, Hazirah; Lim, Choon Liat (North Carolina State University, 2024)
The limited market share and growth of Bumiputera entrepreneurs in domestic furniture and wood product industry in Malaysia remains a long-standing challenge. Therefore, a study to examine the market factors that contribute to the failure to thrive among Bumiputera entrepreneurs, registered with the Malaysian Timber Industry Board, was conducted. The results revealed that most of the respondents were micro-and small-sized enterprises, with sales focused on the domestic and contract markets. They were mostly producing sofa and kitchen cabinets, made to order, and sold in domestic markets within the vicinity. The respondents also indicated that the major challenges that impeded their ability to penetrate and capture market share include the limited production volume, lack of product diversity, limited government contract, and inter-ethnicity business collaboration. The Chi-square and Pearson Product Moment Correlation tests found that the significant challenges were only the limited production volume due to small company size, lack of product diversity, and the limited inter-ethnicity business collaboration among Bumiputera entrepreneurs. Therefore, policymakers should take heed that despite the many years of targeted and affirmative assistance to expand the domestic market share of Bumiputera entrepreneurs, the results remain poor, and inevitably, a new approach to Bumiputera entrepreneurs’ development must be adopted.